Voting in small committees - Paolo Balduzzi; Clara Graziano; Annalisa Luporini (Center for Economic Studies and ifo Institute (CESifo), 2012)
A small committee has to approve/reject a project with uncertain return. Members have different preferences: some are value-maximizers, others are biased towards approval. We focus on the efficient use of scarce information when communication is not guaranteed, and we provide insights on the optimal committee composition. We show that the presence of biased members can improve the voting outcome by simplifying the strategies of unbiased members. Thus, heterogeneous committees perform at least as well as homogeneous committees. In particular, when value-maximizers outnumber biased members by one vote, the optimal equilibrium becomes unique. Finally, allowing members to communicate brings no improvement.
Keywords: D71; D72; 330; voting; small committees; committees composition; communication in committees; Gruppenentscheidung; Wahlverhalten; Kommunikation; Präferenztheorie; Theorie